Experimental Study And Modeling Of Water Retention Curve Of A Silty Soil Compacted And Treated With Cement - Belal Tewfik; Ghembaza Moulay Smaine; Bellia Zoheir (Aceh International Journal of Science and Technology, 2020)
The evaluation of unsaturated soils' fundamental properties is ensured by the characteristic water retention curve for a wide range of soil suction values. However, a minimal number of research works have focused on studying the water retention properties of natural soils and treated with hydraulic binders using soil-water characteristic curves (SWCC). The present work is motivated by the lack of experimental evidence of this type. Firstly, experimental measurements of soil-water characteristic curves of a natural loam soil from the region of Sidi Bel Abbes (Algeria), treated with cement and compacted at Standard Optimum Proctor at an ambient temperature of 20 °C, Were carried out using the methods of the imposition of suction, namely the osmotic method ranging from 0 to 0.05 MPa and the method of saline solutions over a suction range from 0.05 MPa to about 343 MPa respectively. The suction used were applied to four studied mixtures (natural soil, + 2%, + 4% and + 6% cement). At the end of the tests on the drainage-humidification path, the water retention curves for the treated soil at different cement dosage allow us to determine the different state parameters of the treated soil: Degree of saturation (Sr), dry weight (d), void ratio (e) and water content (w). The suction imposition range and the cement dosage significantly influence the water behavior of the material studied. On the other hand, we develop a model of the water behavior of soils treated with cement. This model makes it possible to correctly predict the retention curves at different cement dosage from the experimental measurements performed on samples compacted at Standard Optimum Proctor represented in the plans [suction, degree of saturation] and [suction, moisture content].